Hypocapnia is an independent predictor of in‐hospital mortality in acute heart failure - Wen‐Jing Tang; Bai‐Kang Xie; Wei Liang; Yan‐Zhao Zhou; Wen‐Long Kuang; Fen Chen; Min Wang; Miao Yu (ESC Heart Failure, 2023)
Abstract Aims Acute heart failure (AHF) poses a major threat to hospitalized patients for its high mortality rate and serious complications. The aim of this study is to determine whether hypocapnia [defined as the partial pressure of arterial carbon dioxide (PaCO2) below 35 mmHg] on admission could be associated with in‐hospital all‐cause mortality in AHF. Methods and results A total of 676 patients treated in the coronary care unit for AHF were retrospectively analysed, and the study endpoint was in‐hospital all‐cause mortality. The 1:1 propensity score matching (PSM) analysis, Kaplan–Meier curve, and Cox regression model were used to explore the association between hypocapnia and in‐hospital all‐cause mortality in AHF. Receiver operating characteristic (ROC) curve and Delong's test were used to assess the performance of hypocapnia in predicting in‐hospital all‐cause mortality in AHF. The study cohort included 464 (68.6%) males and 212 (31.4%) females, and the median age was 66 years (interquartile range 56–74 years). Ninety‐eight (14.5%) patients died during hospitalization and presented more hypocapnia than survivors (76.5% vs. 45.5%, P < 0.001). A 1:1 PSM was performed between hypocapnic and non‐hypocapnic patients, with 264 individuals in each of the two groups after matching. Compared with non‐hypocapnic patients, in‐hospital mortality was significantly higher in hypocapnic patients both before (22.2% vs. 6.8%, P < 0.001) and after (20.8% vs. 8.7%, P < 0.001) PSM. Kaplan–Meier curve showed a significantly higher probability of in‐hospital death in patients with hypocapnia before and after PSM (both P < 0.001 for the log‐rank test). Multivariate Cox regression analysis showed that hypocapnia was an independent predictor of AHF mortality both before [hazard ratio (HR) 2.22; 95% confidence interval (CI) 1.23–3.98; P = 0.008] and after (HR 2.19; 95% CI 1.18–4.07; P = 0.013) PSM. Delong's test showed that the area under the ROC curve was improved after adding hypocapnia into the model (0.872, 95% CI 0.839–0.901 vs. 0.855, 95% CI 0.820–0.886, P = 0.028). PaCO2 was correlated with the estimated glomerular filtration rate (r = 0.20, P = 0.001), left ventricular ejection fraction (r = 0.13, P < 0.001), B‐type natriuretic peptide (r = −0.28, P < 0.001), and lactate (r = −0.15, P < 0.001). Kaplan–Meier curve of PaCO2 tertiles and multivariate Cox regression analysis showed that the lowest PaCO2 tertile was associated with increased risk of in‐hospital mortality in AHF (all P < 0.05). Conclusions Hypocapnia is an independent predictor of in‐hospital mortality for AHF.